Prenatal detection of a giant isolated coronary fistula. Issue 3 (4th February 2021) - Walter, Adeline; Calite, Elina; Engels, Alexander C.; Herberg, Ulrike; Breuer, Johannes; Willruth, Arne; Berg, Christoph; Geipel, Annegret; Gembruch, Ulrich
Abstract: Prenatal detection of an isolated congenital coronary artery fistula (ICCAF) requires an examination of the affected fetal hemodynamic situation by the fistula. Early pediatric cardiological presentation is needed, since prenatal changes may have relevant postpartal consequences. Abstract : Prenatal detection of an ICCAF requires an examination of the affected fetal hemodynamic situation by the fistula. Early pediatric cardiological presentation is needed, since prenatal changes may have relevant postpartal consequences.